DESENTRALISASI KEKUASAAN DAN DANA PERIMBANGAN PUSAT DALAM PENGUATAN PEMERINTAHAN PADA DEMOKRASI LOKAL - Nazmudin Nazmudin (NIAGARA Scientific Journal, 2017)
Addressing the issue of dsesentralisasi and balancing funds, regulations on the financial area is the emphasis remains on the distribution of proportion and not to the administration broad authority so that a greater emphasis on the results of natural resources (NR) is considered more profitable rich areas (SDA) and not profitable areas not producing natural wealth. While the source of the general allocation fund, although based on a formula that is more objective and transparent, but tend to be more emphasis on equity and less attention to the side of justice. From some thought it was revealed that in order to anticipate the negative impact of the above then any design of financial balance in addition need to be designed more carefully and take into account regional equity should also be a policy of equalization funds center continues bersendikan elements of the potential capacity of the reception area (assessing the contribution of regions to the central revenue) as well as the guarantee of autonomy regional and local accountability in order to establish the strengthening of local democracy. This paper uses qualitative research methods to examine the data further research.